Occupational Transformation and Social Solidarity in Koya Barat, Papua - La Mochtar Unu (Mandalika Journal of Business and Management Studies, 2026)
Occupational transformation has become a prominent feature of rural–urban transition, influencing not only local economic structures but also patterns of social solidarity. This study examines how occupational transformation has shaped the transition of social solidarity in Koya Barat, a peri-urban transmigration community in Jayapura City, Papua, Indonesia. A qualitative case study approach was employed using participant observation, in-depth interviews, and focus group discussions involving community leaders, government officials, farmers, entrepreneurs, and local residents. Data were analyzed using the interactive model of data reduction, data display, and conclusion drawing. The findings reveal a substantial shift from an agriculture-based economy toward a more diversified service-oriented economy, driven by infrastructure development, population growth, and increasing commercial investment. This occupational diversification has expanded the division of labor and reshaped patterns of social interaction within the community. The study demonstrates that mechanical and organic forms of solidarity coexist during socioeconomic transition rather than replacing one another, with traditional values of mutual assistance remaining alongside increasing functional interdependence. Unlike previous studies that primarily emphasize the economic dimensions of occupational transformation or urban expansion, this study highlights the coexistence of mechanical and organic solidarity as a hybrid form of social cohesion in a peri-urban transmigration community, thereby extending Durkheim's theoretical perspective within the context of developing societies. These findings contribute new empirical evidence on the relationship between occupational diversification and social solidarity and underscore the importance of integrating social cohesion into regional development policies.